2012
DOI: 10.1017/s1049023x12000271
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care at Mass Gatherings: Emergency Medical Services at Large-Scale Rave Events

Abstract: Objective: The objective of this study was to develop comprehensive guidelines for medical care during mass gatherings based on the experience of providing medical support during rave parties. Methods: Study design was a prospective, observational study of self-referred patients who reported to First Aid Stations (FASs) during Dutch rave parties. All users of medical care were registered on an existing standard questionnaire. Health problems were categorized as medical, trauma, psychological, or miscellaneous.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 18 publications
(28 reference statements)
0
41
0
1
Order By: Relevance
“…Sufficient first-aid capability and the quality of security emerged from the results along with other needed services, such as taking care of water supply. Previous studies indicated that on-site medical staff should include health professionals along with first-aid providers [15,18,19,23,40]. According to Locoh-Donou et al [26], absence of free drinking water is strongly associated with patient presentations.…”
Section: Factors To Be Noted In the Emergency Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient first-aid capability and the quality of security emerged from the results along with other needed services, such as taking care of water supply. Previous studies indicated that on-site medical staff should include health professionals along with first-aid providers [15,18,19,23,40]. According to Locoh-Donou et al [26], absence of free drinking water is strongly associated with patient presentations.…”
Section: Factors To Be Noted In the Emergency Planmentioning
confidence: 99%
“…Different factors were shown to have an impact on the need of transport to hospital, the number of patients, and the injury patterns. These include weather [13,14], the level of the on-site medical care [15][16][17][18][19][20][21][22][23], audience profile [24], event type [25][26][27], duration [28], and geographical location [29]. Alcohol and drug use, attendance, and the age and mood of the crowd can also have an effect on the level and the need of medical response [28].…”
Section: Introductionmentioning
confidence: 99%
“…If a similar scenario also occurs in rave attendants in spite of the rewarding properties of the environment, hippocampal dysfunction might contribute to the increasing number of psychological and traumatic medical events, including car accidents, and may significantly compromise working activity and school/academic performance for a few days after rave [55,56]. A prolonged 5-HT depletion in response to environmental stressors might produce tolerance to the detrimental effects of a subsequent exposure, but, on the other hand, might alter the mechanisms of resilience to stress [57][58][59][60] resulting into mood disorders or other stress-related disorders in predisposed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is worth considering how waste collection affects the functioning of the city area in which the mass event is organized, especially when there is a large accumulation of vessels that are disposing of waste. Mass events require extraordinary measures to ensure the safety of participants [30,31], transport accessibility of the venue, and supplies [32]. However, issues related to reverse logistics are also equally important.…”
Section: Theoretical Aspects Of Waste Collection From Yachts and Tallmentioning
confidence: 99%